Comparative study of the effects of fennel with Gelofen on the severity of primary dysmenorrhea: A randomized clinical trial - Roya Motavalli; Samira Shahbazzadegan (Mashhad University of Medical Sciences, 2018)
Introduction: Dysmenorrhea is one of the most common gynecological disorders; so that 50 to 70 percent of women suffer it. Dysmenorrhea is often treated by chemical drugs. However, studies showed that almost half of the population in industrialized countries is already using complementary medicine and alternative therapies. Therefore, this study was performed with aim to compare the effects of fennel and Gelofen on severity of primary dysmenorrhea. Methods: This clinical trial was performed on 72 students residing in dormitories of Islamic Azad University of Ardabil in 2016. Samples with grade 2 and 3 of primary dysmenorrhea were randomly divided in two groups of fennel and Gelofen receivers. The fennel group used 3-5 drop of fennel extract in water or tea three times per day during first 3 days of menstruation and Gelofen group used Gelofen capsule every 6 hours during this period. Both groups used this method for three consecutive cycles. Data collection tool included a dysmenorrhea severity questionnaire according verbal multidimensional scoring criteria. Data were analyzed using SPSS software (version 17) and t-test and chi-square. P < 0.05 was considered significant. Results: Both fennel and Gelofen reduced the severity of pain from severe and moderate to mild and no pain, but there was no significant difference between the two groups of fennel and Glofen in improvement of dysmenorrhea (p>0.05). Conclusion: The use of both methods of fennel and Glofen was effective in reducing the pain of primary dysmenorrhea and pain reduction was similar in both groups. Regarding the high prevalence of dysmenorrhea in female, the use of fennel in the relief of dysmenorrhea is recommended.